Women, writing, and language in early modern Ireland - Coolahan, Marie-Louise (Oxford University Press, 2010)
This study discusses women's writing in early modern Ireland. It explores the ways in which women contributed to the power struggles of the period, how they strove to be heard, forged space for their voices, and engaged with new and native language-traditions to produce petition-letters, depositions, poetry, and autobiography.